Border cities and territorial development - Medeiros, Eduardo (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This monograph analyses the role of border cities to promote territorial development processes in border regions across the world. It embraces not only the scientific fields of regional and urban studies, but also addresses territorial (urban, local, regional) development and planning theories, as well as the effects of development policies applied to border regions in both Europe and North America. In essence, the book offers a full toolkit of border regions' territorial development knowledge and, in particular, advances a range of policy development proposals. It provides a comprehensive introduction to contemporary thinking about how border cities can play a decisive role in boosting territorial development processes in border regions. The book is divided into three main sections. The first presents a theoretical framework on the role of border cities in promoting territorial development and planning in border regions. The second section debates current mainstream policies focusing on supporting border regions and specifically border cities in the EU, the UK and North America. Finally, a third section presents a wealth of updated knowledge, based on the analysis of several concrete case studies: border cities from both Europe (north, south, east and west), and North America (Canada, USA and Mexico). The chapters are written by some of the most renowned authors on the subject, including scholars from several European and North American countries, as well as the secretary generals of three European border regions associations (AEBR, MOT and CESCI). The book will thoroughly prepare students and provide knowledge to academics and policymakers in the fields of urban and regional planning and development studies, human geography, economic development, EU policies, border regions, and policy impacts"--
Territorial development and border cities. A theoretical debate / Eduardo Medeiros -- The challenge for economic development and innovation in border regions / Bjørnar Sæther -- Cross-border planning and border cities. A theoretical proposal / Antoine Decouville, Frédéric Durand and Christophe Sohn -- European policies and border cities / Bernard Reitel, Pauline Pupier, and Birte Wassenberg -- U.S. border cities : policies, space, and Identity / Francisco Lara-Valencia and Lawrence A. Herzog -- Brexit and the policy landscape for cities at the Ireland-Northern Ireland border / Anthony Soares -- French border cities and territorial development trends / Jean Peyrony, Aurélien Biscaut, Thibault Devillard and Jean Rubio -- Germany-Danish border cities and territorial development trends / Martin Klatt -- Cross-border agglomeration tendencies between Hungary and Slovakia / Mátyás Jaschitz and Gyula Ocskay -- Border cities in Portugal-Spain and territorial development trends / Eduardo Medeiros and Paulo Neto -- USA-Canada border cities and territorial development trends / Emmanuel Brunet-Jailly -- USA-Mexico border cities and territorial development trends / Sergio Peña.
OCLC-licensed vendor bibliographic record.
Keywords: City planning -- Case studies; Borderlands -- Case studies; Regional planning -- Case studies; Economic development -- Case studies; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Urban & Regional; BUSINESS & ECONOMICS / Development / Sustainable Development